Expression of Protease Activated Receptor-1 in Chronic Periodontitis - Bueno da Silva, Henrique Aparecido; Euzebio Alves, Vanessa Tubero; Spolidório, Luis Carlos [UNESP]; Cesar Neto, Joao Batista; Eichler, Rosangela Santos; Catelli de Carvalho, Maria Helena; Holzhausen, Marinella (Amer Acad Periodontology, 2014)
Background: Protease activated receptor-1 (PAR(1)) activation by thrombin may play a role in repair and homeostasis of periodontal tissues. The main objective of this study is to investigate PAR(1) expression in patients with periodontitis, before and after non-surgical periodontal treatment, and to associate its expression with the presence of inflammatory biomarkers and PAR(2) expression.Methods: Gingival crevicular fluid (GCF) samples and clinical parameters, including probing depth, clinical attachment level, bleeding on probing, and gingival and plaque indices, were collected from periodontally healthy individuals and patients with moderate chronic periodontitis (CP) before and 6 weeks after periodontal non-surgical treatment. PAR(1) and PAR(2) messenger RNA (mRNA) at the GCF were evaluated by quantitative polymerase chain reaction (qPCR). Flow cytometry analysis identified the GCF PAR(1)-expressing cells. GCF inflammatory biomarkers were also determined.Results: Clinical parameters were significantly improved after therapy (P < 0.01). The qPCR analysis showed that, before therapy, PAR(1) mRNA levels in CP were similar to controls. Periodontal treatment led to increased PAR(1) expression in CP (P < 0.05). PAR(1) expression was inversely correlated to PAR(2) expression and with interleukins 6 and 8, tumor necrosis factor-alpha, interferon-gamma, and matrix metalloproteinase-2 levels.Conclusions: Periodontal treatment results in PAR(1) overexpression in the GCF, and PAR(1) expression is associated with decreased expression of inflammatory biomarkers and inversely correlated to PAR(2) expression in the GCF. Therefore, the data suggest the importance of PAR(1) mediating the known anabolic actions of thrombin in the periodontium.
Keywords: Biological markers; chronic periodontitis; gene expression; immunity, innate; inflammation; wound healing